Operational modal analysis of a spar-type floating platform using frequency domain decomposition method - Ruzzo, Carlo; Failla, Giuseppe; Collu, Maurizio; Nava, Vincenzo; Fiamma, Vincenzo; Arena, Felice (MDPI, 2016)
System identification of offshore floating platforms is usually performed by testing small-scale models in wave tanks, where controlled conditions, such as still water for free decay tests, regular and irregular wave loading can be represented. However, this approach may result in constraints on model dimensions, testing time, and costs of the experimental activity. For such reasons, intermediate-scale field modelling of offshore floating structures may become an interesting as well as cost-effective alternative in a near future. Clearly, since the open sea is not a controlled environment, traditional system identification may become challenging and less precise. In this paper, a new approach based on Frequency Domain Decomposition (FDD) method for Operational Modal Analysis is proposed and validated against numerical simulations in ANSYS AQWA v.16.0 on a simple spar-type structure. The results obtained match well with numerical predictions, showing that this new approach, opportunely coupled with more traditional wave tanks techniques, proves to be very promising to perform field-site identification of the model structures.
Keywords: Frequency Domain Decomposition; output-only system identification; damping of offshore structures